The gut microbiome in human neurological disease: A review. Issue 3 (20th March 2017) - Tremlett, Helen; Bauer, Kylynda C.; Appel‐Cresswell, Silke; Finlay, Brett B.; Waubant, Emmanuelle
Abstract : Almost half the cells and 1% of the unique genes found in our bodies are human, the rest are from microbes, predominantly bacteria, archaea, fungi, and viruses. These microorganisms collectively form the human microbiota, with most colonizing the gut. Recent technological advances, open access data libraries, and application of high‐throughput sequencing have allowed these microbes to be identified and their contribution to neurological health to be examined. Emerging evidence links perturbations in the gut microbiota to neurological disease, including disease risk, activity, and progression. This review provides an overview of the recent advances in microbiome research in relation to neuro(auto)immune and neurodegenerative conditions affecting humans, such as multiple sclerosis, neuromyelitis optica spectrum disorders, Parkinson disease, Alzheimer disease, Huntington disease, and amyotrophic lateral sclerosis. Study design and terminology used in this rapidly evolving, highly multidisciplinary field are summarized to empower and engage the neurology community in this "newly discovered organ." Ann Neurol 2017;81:369–382